The Importance of Quality Service in Increasing Customer Loyalty: A Case Study of Traditional Ships - Subehana Rachman (Greenation Research & Yayasan Global Resarch National, 2024)
This study investigates the influence of service quality on customer perception, satisfaction, and loyalty in North Jakarta. The study employs a quantitative research method, gathering data from 28 tourists who utilize the port's services. Researchers collected data for one month by directly distributing questionnaires. We carried out the data analysis using SPSS version 25. The analysis results showed a significant relationship between service quality, customer satisfaction, and loyalty. Better service quality and high customer satisfaction tend to increase customer loyalty. This study sheds light on the significance of focusing on service quality and customer satisfaction as a strategy to maintain and increase customer loyalty in the future. However, there are still other factors that need to be considered in understanding customer loyalty, such as price, promotion, and brand image. Further research, taking into account these additional variables, can provide a more complete understanding of the factors that influence customer loyalty at traditional ports such as North Jakarta.